Global soybean trade intensifies the impacts of dietary transition on human mobility - Nan Jia; Hongbo Yang; Xin Lan; Yinshuai Li; Yongze Song; Zehua Zhang; Wen Song; Rui Zhao; Tianwu Ma; Ruishan Chen (iScience)
Summary: Soybeans have experienced massive growth in trade due to diet transitions. Large imports reduce expected returns for soybean growers in importer countries, influencing occupational choices and potentially facilitating population mobility, though the distant correlation’s impact remains unclear. We develop a framework integrating diet dynamics, trade indexes, and human mobility. We found: (1) dietary transition promotes human mobility through global soybean trade; (2) rural areas contribute far less than urban areas, illustrating decoupling between rural regions and international trade; (3) enhancing rural-trade coupling could improve dietary and crop flow in rural regions; (4) the study provides a new perspective on how dietary transition promotes human mobility. These findings help policymakers identify soybean trade strategies for socioeconomic development and formulate interventions to optimize population distribution. By addressing rural decoupling, we emphasize aligning rural areas with global trade to mitigate mobility pressures and socioeconomic disparities, without altering original terms.